Relation between the Epoxy Resin Curing and the Mechanical Properties of the Composite Reinforced with Aramid/Glass (Research, Society and Development, 2021)
DGEBA has a widespread use in the manufacture of polymer composites to obtain different elements of structural engineering. The mechanical properties can be predicted by the physical-chemical knowledge of the processing conditions of the resin components, and of their storage and handling conditions. This study aimed to characterize the functional groups, as well as the curing behavior of a batch of resin with different times of storage and storage control, using FTIR spectroscopy. The resin was used in the matrix of the composites with textile reinforcement, for which the mechanical behavior was examined through tensile and impact tests. It was noticed that the degradation effect in the polymer structure causes a reduction in the tensile strength and in the impact energy of the composite.